Aktualisasi Nilai Sila Ketiga Pancasila: Menjaga Persatuan di Era Globalisasi yang Penuh Tantangan - Ture Ayu Situmeang; Yakobus Ndona (Jurnal Akuntan Publik, 2025)
Globalization is a term that has to do with the increasing interconnectedness and interdependence between nations and people around the world through trade, investment, travel, popular culture, and other forms of interaction, so that the boundaries of a country become increasingly narrow. The values of Pancasila, especially the values contained in the third principle, namely "Indonesian Unity," are very relevant and important to be actualized in everyday life. The author uses the Literature Study method, which is defined by Nazir (2013) as a systematic process of tracing various literature sources relevant to the research topic to obtain the necessary information and materials. The results showed that the Third Precept of Pancasila has a very strategic role in facing challenges in the era of globalization. By instilling the values of unity, Indonesia can maintain national identity, overcome economic challenges, preserve culture, increase tolerance, and strengthen political positions in the international arena